FEATURES OF ENGLISH AND UZBEK COMPARISONS IN LINGUOCULTURAL ASPECT - Sodikova Sayyorakhan Talabovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyses English and Uzbek comparisons in the lingvoculturological aspect.The peculiarities of English and Uzbek comparisons , differences have been shown.